Selection of oligosaccharides as prebiotic for probiotic Lactobacillus strains and their effects on performance of broiler chickens - Poothan Mookiah, Saminathan (2011)
Currently, a variety of probiotic bacterial strains and prebiotic oligosaccharides have been used singly or in combinations as synbiotics (probiotics + prebiotics) to enhance the health and well-being of the host animals. However, very often, synbiotics are produced without studying and selecting suitable prebiotics for specific probiotic bacterial strains. In the present study, a series of experiments was carried out to investigate the growth of 11 probiotic Lactobacillus strains in prebiotic oligosaccharides in vitro to select a suitable prebiotic for developing a synbiotic, and to determine the effects of the prebiotic singly and in combination as a synbiotic on the growth performance of chickens in vivo. In a preliminary study, the growth of the 11 Lactobacillus strains was assessed in 10 commercially available prebiotic oligosaccharides in vitro. The results showed that the utilization of oligosaccharides was highly variable among the 11 Lactobacillus strains and considerable strain differences (P< 0.05) were observed. Prebiotic isomaltooligosaccharides (IMO) supported good growth for most of the Lactobacillus strains, followed by galactooligosaccharides (GOS), gentiooligosaccharides (GTO) and fructooligosaccharides (FOS). Oligosaccharides such as Raftilose L60, Raftilose P95, Raftiline LS, and mannanoligosaccharides (MOS) were poorly utilized by all the Lactobacillus strains. The four prebiotic oligosaccharides, IMO, GOS, GTO and FOS, which supported good growth of most of the Lactobacillus strains were selected for further studies on the growth kinetics and organic acids (acetic and lactic acids) production of the Lactobacillus strains. The results of the growth kinetics study also showed variations in the specific growth rates (μ) and growth patterns of the 11 Lactobacillus strains on GOS,IMO, GTO and FOS. Productions of acetic and lactic acids appeared to be growth associated and correlated with the growth patterns of the Lactobacillus strains on different prebiotic oligosaccharides. Among the four selected prebiotics, IMO was found to provide the best growth and higher specific growth rates, with generation of high concentrations of lactic and acetic acids of most of the Lactobacillus strains, and was therefore considered as a suitable prebiotic for the strains. The efficacy of prebiotic IMO was then evaluated singly and in combination as a synbiotic in vivo in a chicken feeding trial. The results of the chicken feeding trial showed that supplementation of probiotic (0.1% of a mixture of the 11 Lactobacillus strains) (PRO), 0.5% prebiotic IMO (PRE05), 1.0% prebiotic IMO (PRE10), synbiotic with 0.5% prebiotic IMO (SYN05) and synbiotic with 1.0% prebiotic IMO (SYN10) could improve body weight, weight gain and feed efficiency of broiler chickens, and there were no significant differences between the treatments. The supplementation of probiotic, prebiotics and synbiotics also significantly (P < 0.05) increased the caecal populations of lactobacilli and bifidobacteria, decreased the caecal E.coli and total aerobe populations, increased the caecal VFA and non-VFA concentrations, and lowered the serum total cholesterol, LDL cholesterol and triglycerides concentrations; but there were no significant differences in the relative weights of the organs such as the heart, liver, spleen and bursa as compared to the control. In all the parameters studied, the synbiotics did not show a twofold synergistic effect, although in some parameters (e.g caecal VFA and non-VFA concentrations) there were significant increases when compared to those of probiotic or prebiotic alone. The results of the chicken feeding trial indicated that prebiotic IMO (0.5 or 1.0%) and its synbiotic could be as effective as probiotic in improving the performance of broiler chickens and in conferring other health benefits on the chickens